Pre-natal, clonal origin of acute lymphoblastic leukaemia in triplets - Zuna, Jan; Muzikova, Katerina; Ford, Anthony M; Maia, Ana Teresa; Krejci, Ondrej; Tousovska, Katerina; Oravkinova, Irina; Greaves, Mel; Trka, Jan (Leukemia & lymphoma, 2003)
A unique case of ALL in three monozygotic triplets diagnosed at the age of 24, 27 and 37 months is described. Archived bone marrow smears were available for molecular analysis of immunoglobulin heavy chain (IGH) and IGK genes and T-cell receptor (TCR)-delta and gamma gene rearrangements. A shared IGH rearrangement was found in triplets "A" and "B", and an identical rearrangement of TCR-delta in triplets "B" and "C". These data suggest a common, monoclonal initiation of ALL in one of these three triplets, followed by dissemination of clonal progeny to the other twins via vascular anastomoses within the single, monochorionic placenta that they shared in utero. Differences in IGH rearrangements in diagnostic samples also indicates divergent subclonal evolution of the original "pre-leukaemic" clone.
Keywords: Triplets; Bone Marrow; Genes, T-Cell Receptor delta; Humans; buněčný rodokmen; Twins, Monozygotic; Immunoglobulins; Sequence Analysis, DNA; klonování DNA; Female; dospělí; genová přestavba T-lymfocytů; dvojčata monozygotní; Genes, T-Cell Receptor gamma; lidé; geny TcR delta; genová přestavba - gama řetězec receptoru antigenů T-buněk; Cell Lineage; geny pro imunoglobuliny; předškolní dítě; geny TcR gama; sekvenční analýza DNA; Adult; ženské pohlaví; Genes, Immunoglobulin; trojčata; kostní dřeň; polymerázová řetězová reakce; Polymerase Chain Reaction; Gene Rearrangement; Gene Rearrangement, gamma-Chain T-Cell Antigen Receptor; Gene Rearrangement, T-Lymphocyte; akutní lymfatická leukemie; genová přestavba; Cloning, Molecular; Child, Preschool; Precursor Cell Lymphoblastic Leukemia-Lymphoma; imunoglobuliny